Evaluation of Short-Chain Antimicrobial Peptides With Combined Antimicrobial and Anti-inflammatory Bioactivities for the Treatment of Zoonotic Skin Pathogens From Canines - Tang, Qiyu; Yang, Chunyi; Li, Weitian; Zhang, Yuhang; Wang, Xinying; Wang, Weixin; Ma, Zhiling; Zhang, Di; Jin, Yipeng; Lin, Degui (Frontiers in Microbiology, 2021)
The incidence of zoonotic Staphylococcus pseudintermedius and Microsporum canis infections is rapidly growing worldwide in the context of an increasing frequency of close contact between animals and humans, presenting challenges in both human and veterinary medicine. Moreover, the development of microbial resistance and emergence of recalcitrant biofilms, accompanied by the insufficiency of new antimicrobial agents, have become major obstacles in treating superficial skin infections caused by various microbes including S. pseudintermedius and M. canis. Over recent years, the prospects of antimicrobial peptides as emerging antimicrobials to combat microbial infections have been demonstrated. In our study, two novel short-chain peptides, namely allomyrinasin and andricin B, produced by Allomyrina dichotoma and Andrias davidianus, were revealed to exhibit potent antimicrobial efficacy against clinical isolates of S. pseudintermedius and M. canis clinical isolates with remarkable and rapid fungicidal and bactericidal effects, while allomyrinasin exhibited inhibition of biofilm formation and eradication of mature biofilm. These peptides displayed synergistic activity when combined with amoxicillin and terbinafine against S. pseudintermedius and M. canis. Cytoplasmic leakage via cytomembrane permeabilization serves as a mechanism of action. Extremely low haemolytic activity and serum stability in vitro, as well as superior anti-infective efficacy in reducing bacterial counts and relieving the inflammatory response in vivo were detected. The potent antibacterial, antifungal and anti-inflammatory activities of allomyrinasin and andricin B might indicate promising anti-infective alternatives for the treatment of S. pseudintermedius and M. canis infections in the context of human and veterinary medicine.